2020
DOI: 10.1016/j.neucli.2020.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalogram (EEG) in COVID-19: A systematic retrospective study

Abstract: Objectives.-Although rare, neurological manifestations in SARS-CoV-2 infection are increasingly being reported. We conducted a retrospective systematic study to describe the electroencephalography (EEG) characteristics in this disease, looking for specific patterns. Methods.-EEGs performed in patients with positive PCR for SARS-CoV-2 between 25/03/2020 and 06/05/2020 in the University Hospital of Bicêtre were independently reviewed by two experienced neurologists. We used the American Clinical Neurophysiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
83
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(103 citation statements)
references
References 16 publications
13
83
1
6
Order By: Relevance
“…Additional three article were excluded as the relationship between brain abnormalities and COVID-19 infection was noted by the authors as improbable. In detail, the authors attributed reported brain abnormalities rather to other/pre-existing medical conditions, previous pathological situations or interpreted them as potentially coincidental with COVID-19 (Morrasi et al, 2020;Degeneffe et al, 2020;Petrescu et al, 2020). Therefore, we entered a total of 26 articles (including 21 case reports, and 5 cohort studies) into the final synthesis.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Additional three article were excluded as the relationship between brain abnormalities and COVID-19 infection was noted by the authors as improbable. In detail, the authors attributed reported brain abnormalities rather to other/pre-existing medical conditions, previous pathological situations or interpreted them as potentially coincidental with COVID-19 (Morrasi et al, 2020;Degeneffe et al, 2020;Petrescu et al, 2020). Therefore, we entered a total of 26 articles (including 21 case reports, and 5 cohort studies) into the final synthesis.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…In total, 6890 patients were included in the studies. Among the 68 studies on the CNS effects, 46 were case reports [16,17,, followed by 10 retrospective studies [64][65][66][67][68][69][70][71][72][73], 4 observational cohort studies [74][75][76][77], 3 prospective studies [78][79][80], 3 case-control studies [81][82][83] and 2 cross-sectional studies [84,85]. Among the 21 studies regarding PNS disorders, there were 19 case reports [86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104], 1 prospective study [78] and 1 retrospective study [68].…”
Section: Categorization and Characteristics Of The Selected Studiesmentioning
confidence: 99%
“…F, female; OR, odd ratio. * Other Neurological Conditions were the following: brain edema [41]; headache [78]; impaired consciousness [68,78]; dizziness [78]; acute mania [45]; intracranial hypertension [48]; electroencephalography alterations [70]; vasculopathy [72]; and brain and spine demyelination [61].…”
Section: Effects Of Sars-cov-2 On Cnsmentioning
confidence: 99%
See 1 more Smart Citation
“…The third study, a single institution retrospective review from France (Petrescu et al 12 ), reports 40 consecutive routine EEGs from 36 patients who tested positive for COVID, after excluding brain death studies and asymptomatic patients, half of the patients from the ICU. Electroencephalograms were normal or nearly normal in a little more than half of the recordings (57.5%).…”
Section: Commentarymentioning
confidence: 99%